O006 Lumican: a novel gycoprotein mediating inflammation in osteoarthritis. (21st February 2018) - Barreto, G; Senturk, B; Colombo, L; Neidenbach, P; Salzmann, G; Rottmar, M; Zenobi-Wong, M
Abstract : Introduction: Lumican (LUM) is major extracellular matrix protein which is present in glycoprotein format in adult articular cartilage. Recently, LUM was show to augment pathogen-associated molecular patterns (PAMPs) activation of the TLR4 signalling cascade. Given that TLR4 is highly associated with inflammation in rheumatic disease, we aim to decipher the LUM role in Osteoarthritis and TLR4 associated inflammation. Objectives: To measure LUM in synovial fluid from patients with arthritic conditions and to study the role of LUM on TLR4 activation in osteoarthritis. Methods: Synovial fluid (SF) was obtained from knee meniscus tear (n=11), first carpometacarpal (CMC-I) OA (n=11) and knee OA (n=40) patients. LUM glycoprotein levels were analysed by enzyme-linked immunosorbent assay (ELISA). Human monocytes were isolated from healthy individuals and differentiated into M1-like and M2-like macrophages by lipopolysaccharide (LPS) and interleukin-4, respectively. LUM (1 ug/ml) was added either together with macrophage polarisation inducers or alone. Primary chondrocytes and OA cartilage explants were stimulated for 24 hour with LUM (1 µg/ml), LPS (10 ng/ml), or a combination of both. Conditioned media was analysed for selected secreted molecules by xMAP technology. Macrophages surface expression markers CD197 and CD206 were analysed by Fluorescence-Activated Cell Sorting (FACS). Cartilage explants were immunofluorescently double stained for collagen type II and X. Results: LUM glycoprotein levels were significantly upregulated in knee OA SF vs. controls. In normal articular chondrocytes, LUM combined with LPS caused an upregulated secretion of catabolic markers characteristic of OA such as IL-6, MMP-1, and MMP-13 in comparison to LPS stimulation. LUM alone had no observable effects. A similar response occurred in cartilage explant cultures, with increased MMP-1 secretion levels and marked cartilage degradation with the LPS/LUM combination. Interestingly, LUM stimulation with the polarisation inducer, LPS for M1, and IL-4 for M2 macrophages, upregulated M1 macrophage secretion of TNF-alpha and downregulated IL-10 secretion in M2 macrophages relative to control and LUM alone. FACS results followed the same trend, with increased CD197 expression in LUM/LPS combination vs. LUM alone or control, and downregulation of CD206 expression when LUM/IL-4 combination vs. LUM alone or control. Conclusions: The results presented here show that LUM is highly upregulated in SF of OA and RA patients. In addition, we observed that TLR-expressing chondrocytes do not respond to LUM, however LUM augmented the LPS-induced TLR4 signalling cascade and consequently the catabolic response. Moreover, we also demonstrate the ability of LUM to upregulate M1 macrophage and downregulate M2 macrophage polarisation. Our findings strongly support a pathogenic role of LUM, as mediator of PAMP-induced TLR-4 activation of inflammation, cartilage degradation and macrophage polarisation in OA and other rheumatic diseases. Disclosure of interest: None declared